A selectively contacted double-sided TOPCon battery structure and preparation method thereof
By preparing a multi-layered passivation contact layer on the front and back of the TOPCon battery, and using BF3 for in-situ doping, the problem of difficulty in achieving large-scale production of the front local polycrystalline silicon passivation process is solved, and the dual improvement of low contact resistance and high photoelectric conversion efficiency is achieved.
Patent Information
- Application Number
- CN202510026114.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-08
AI Technical Summary
TOPCon batteries perform well in efficiency and market share, but their potential to further improve efficiency is limited by technical bottlenecks, especially the frontal local polycrystalline silicon passivation process is difficult to achieve large-scale production, resulting in increased contact resistance and loss of photoelectric conversion efficiency.
The double-sided TOPCon battery structure with selective contact is adopted to improve the photoelectric conversion efficiency of the battery by forming selective contact on the p-type polysilicon layer. The specific method includes preparing a passivation contact layer of a multi-layer structure on the front and back sides, using BF3 as a boron source for in-situ doping, combining PECVD and laser modification technology to optimize the thickness and doping concentration of the polycrystalline silicon layer.
It is achieved to optimize the thickness of the polysilicon layer while ensuring low contact resistance, reduce parasitic absorption, and significantly improve the photoelectric conversion efficiency of the battery.
Smart Images

Figure CN119451285B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a selectively contacted double-sided TOPCon cell structure and a preparation method thereof. Background Art
[0002] TOPCon (Tunnel Oxide Passivating Contact) cell technology, as an advanced N-type silicon solar cell structure, has made significant progress in improving photoelectric conversion efficiency with its excellent surface passivation characteristics and low surface recombination rate. This technology uses a thin oxide layer (usually silicon oxide) deposited on the surface of the silicon wafer and forms a doped polycrystalline silicon (poly-Si) layer on top of it, which can effectively suppress the recombination of electrons and holes, thereby improving the open circuit voltage and fill factor of the cell. However, despite the excellent performance of TOPCon cells in terms of efficiency and market share, its potential for further efficiency improvement is limited by many technical bottlenecks. Among them, the front local polysilicon passivation (poly finger) process is difficult to achieve large-scale production, which has become one of the key factors restricting the further improvement of TOPCon cell efficiency.
[0003] In the front structure of the TOPCon battery, the polysilicon layer (p-Poly or p-Poly-Si) is the key passivation contact layer, which is used to reduce carrier recombination, provide charge transfer channels, and form good electrical contact with the silver paste. However, the passivation of front polysilicon (especially the passivation structure of local polysilicon) is difficult to produce on a large scale, mainly reflected in the matching problem between metal contact and polysilicon. In the process of contact between the front p-Poly layer and the silver paste, it is very important to form a good ohmic contact. If the p-Poly layer is too thin, it may not be able to form an effective electrical contact, resulting in increased contact resistance and affecting battery performance. If the p-Poly layer is too thick, it will cause greater parasitic absorption, resulting in a loss of photoelectric conversion efficiency. Therefore, how to optimize the thickness of the polysilicon layer while ensuring low contact resistance has become a technical problem.
[0004] In particular, the solid solubility of boron atoms in polysilicon is low. This characteristic makes it difficult for boron atoms to reach a high concentration during the boron doping process of the front p-Poly layer. This difference in solid solubility results in a low concentration of boron atoms when using conventional boron doping methods (for example, using diborane B2H6 for hydrogen bridge bond doping), resulting in limited electrical properties of the p-Poly layer. This not only affects the conductivity of polysilicon, but also makes it more difficult to thin the p-Poly layer. The significance of p-Poly thinning is to reduce the thickness of the silicon layer and reduce parasitic absorption, but the limitation of boron concentration makes it impossible for the thinned p-Poly layer to form a good ohmic contact, thereby increasing the contact resistance of the battery and limiting its efficiency improvement. This makes the challenges of p-Poly thinning to slurry contact and composite balance much higher than that of n-Poly.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The main purpose of the present invention is to provide a method for preparing a double-sided TOPCon cell structure with selective contact, the core of which is to improve the photoelectric conversion efficiency of the cell by selectively forming contact on the p-type polycrystalline silicon (p-poly Si) layer. Not only does it have excellent photoelectric performance on the front side, but the back side is also optimized to capture more light that is not absorbed by the front side, further improving the overall power generation efficiency and thus improving the photoelectric conversion efficiency of the cell.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a selectively contacted double-sided TOPCon battery structure comprises the following steps:
[0009] S1: Select N-type silicon wafer as the battery substrate and perform double-sided texturing;
[0010] Preferably, N-type silicon wafers with a resistivity of 0.5-2Ω.cm and a minority carrier lifetime of >10ms are used for texturing to remove damage and form a pyramid structure for surface light trapping. The texturing liquid (KOH: additive = 4:1-10:1) is used, the temperature is maintained at 75-85°C, and the time is about 4-6 minutes for rapid texturing, and the thinning amount is controlled at 0.1-0.3g.
[0011] S2: sequentially preparing a P+ layer and a P++ layer on the textured surface of the front side of the substrate, and depositing a mask layer on the surface at the same time; wherein the P+ layer is a first passivation contact layer formed by boron diffusion or in-situ boron doping using PECVD, and the P++ layer is a second passivation contact layer formed by in-situ boron doping using PECVD; the first passivation contact layer and the second passivation contact layer use BF3 as a boron source;
[0012] When diborane is doped, the doping efficiency and deposition rate are high, easily reaching 1×10 20 atoms / cm 3 However, since a large amount of dust will be generated during the high-temperature (350°C) deposition process and diborane is easily decomposed, only a low-temperature deposition process (300°C) can be used. The low-temperature deposition process will cause the quality of the tunneling oxide layer to deteriorate, and it will be easily destroyed during the high-temperature annealing process. In addition, the inward expansion of boron is more serious, and the diffusion depth and uniformity of boron are difficult to control during the annealing process.
[0013] In the present invention, the first passivation contact layer and the second passivation contact layer use BF3 as a boron source; BF3 is a planar triangular molecule, in which boron atoms are sp 2 The hybrid orbital forms a covalent bond with three fluorine atoms, and due to the strong electronegativity of F atoms, BF3 is more likely to separate B atoms. Therefore, in theory, using BF3 as a boron source for in-situ doping of B can increase the concentration of effective boron atoms, thereby ensuring good contact conditions, reducing the thickness of poly Si, thereby reducing parasitic absorption and greatly improving the efficiency of the battery.
[0014] However, direct introduction of BF3 has no effect on the deposition rate, but it will reduce the doping efficiency and make the B doping concentration lower. Because BF3 has a lower ionization rate than diborane, this low ionization efficiency has a good correlation with the atomic concentration ratio of B / F in the polysilicon film. The addition of F on the surface inhibits the ionization of B, so that the doping concentration (platform area) can only reach 2-5×10 19 atoms / cm 3 interval.
[0015] On this basis, the BF3-doped poly layer may undergo boron internal diffusion when the annealing temperature is ≥920°C, causing the doping concentration of the substrate silicon to reach 1×10 19 atoms / cm 3; This is because fluorine doping significantly increases the diffusion coefficient of boron in silicon oxide. At different concentrations of fluorine doping, the boron diffusion coefficient is greater than that without fluorine doping. The higher the fluorine doping dose, the higher the boron diffusion coefficient. Fluorine doping also significantly increases the diffusion coefficient of boron in nitrogen-doped oxides, and its effect is similar to that of silicon oxide. In this case, the doping concentration has no significant improvement by adjusting parameters such as flow, power, and temperature, and the internal expansion of boron is only alleviated under specific conditions.
[0016] The present invention utilizes a special plasma treatment method to not only improve the boron doping efficiency, but also reduce the consumption of boron source, and the maximum doping concentration can reach 1×10 20 atoms / cm 3 The above results show that the consumption of BF3 is reduced (the overall cost is also reduced), the internal expansion of boron is also significantly improved, and there is no internal expansion of boron at the annealing temperature of 880-980℃ (880-920℃ is the best).
[0017] Preferably, the first passivation contact layer is SiOx1 / p1-poly (p + ), the second passivation contact layer is SiOx2 / p2-poly (p ++ );
[0018] When the N+ layer is a single-layer passivation contact layer, the single-layer passivation contact layer is SiOx / n-poly (n + );
[0019] When the N+ layer is a double-layer passivation contact layer, the double-layer passivation contact layer is SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ).
[0020] The present invention can produce the following four battery structures:
[0021] (1) From the inside to the outside, the front side is composed of a boron diffusion layer, SiOx2 / p2-poly (p ++ ), the back side is SiOx / n-poly (n + );
[0022] (2) From inside to outside, the front side is SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ ), the back side is SiOx / n-poly (n + );
[0023] (3) From the inside to the outside, the front side is composed of a boron diffusion layer, SiOx2 / p2-poly (p ++ ), the back side is SiOx1 / n1-poly (n +) / SiOx2 / n2-poly(n ++ );
[0024] (4) From inside to outside, the front side is SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ ), the back side is SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ).
[0025] Wherein, when the P+ layer is boron diffused, step S2 includes:
[0026] Using diborane as the boron source, boron diffusion is carried out on the textured surface of the substrate to form a PN junction. Specifically, the temperature is 850-1100℃ for doping and oxidation, the BSG thickness is controlled at 90-150nm, the doping square resistance is controlled at 200-400ohm / sq, and the peak concentration of boron atoms is 1×10 18 -1×10 19 atoms / cm 3 ; While forming a PN junction, these doped boron atoms also passivate the surface, reducing the recombination of carriers.
[0027] Use green skin / green nano / purple skin / purple nano laser to modify BSG in the front contact area; loosen or remove the BSG in the contact area, and the removed contact area, i.e. the laser area, is used as the grid line printing area. The width of the contact area is 80-200um, and the groove HF dip (2%-15%) is used to clean and remove the BSG in the contact area;
[0028] Then, SiOx2 / p2-poly (p ++ ), and a mask layer is deposited on the surface. The thickness of SiOx2 is 1-3nm, the thickness of p2-poly is 50-300nm, and the peak concentration of effective boron atoms is 1×10 19 -8×10 20 atoms / cm 3 , the thickness of the outer mask is 10-100nm BSG.
[0029] SiOx2 / p2-poly(p ++ )BF3 is used as a boron source; high-temperature boron diffusion is suitable for forming a thick boron expansion layer, but when combined with a multi-layer poly structure, parasitic absorption will increase, resulting in a decrease in photoelectric conversion efficiency. The poly layer prepared by BF3 in the present invention is thin and has high doping efficiency, which reduces parasitic absorption and improves battery efficiency.
[0030] The PECVD process has the advantage of low-temperature deposition and can deposit boron-doped films without damaging the silicon substrate. The subsequent annealing process activates the boron atoms in the boron-doped layer, allowing it to form an effective electrical contact in the silicon substrate. In PECVD, the excitation of the plasma causes BF3 to decompose, producing active boron atoms and other fragments. The active boron atoms react with gases such as silane (SiH4) and are deposited on the textured surface of the substrate to form a doped polysilicon layer (poly-Si). The SiOx / p-poly structure generated by this reaction can reduce surface recombination to a certain extent while ensuring good electrical contact.
[0031] The present invention prepares a boron diffusion layer and SiOx2 / p2-poly (p ++ ) composite structure, the non-contact area is SiOx2 / p2-poly (p ++ ) is removed to form a selective contact of poly, and the contact area is boron diffusion layer + SiOx2 / p2-poly (p ++ ) composite structure, the non-contact area is a boron diffusion layer. This achieves good contact and poly thinning.
[0032] The innovation of the present invention lies in the front selective doping, and the heavily doped area is a boron diffusion + SiOx2 / p2-poly stacked structure: among them, a boron diffusion layer must be prepared first, and high-temperature doping is placed in the first step. The boron diffusion doping temperature is as high as 1100 degrees, and the annealing temperature of in-situ doping p-poly by PECVD should not exceed 900 degrees. When the annealing temperature rises from a lower level to a certain range (such as 500°C to 700°C), the film structure may first transform into an amorphous phase and then completely crystallize. In this process, the resistivity and temperature coefficient of resistance of the film will decrease monotonically with the increase of doping concentration and annealing temperature. Therefore, treatment within different temperature ranges may affect the crystal structure and performance of the film. Excessively high annealing temperatures may lead to a decrease in film performance, such as increased film density, increased lattice defects, or increased surface recombination rate due to hydrogen escape, reducing the passivation effect and battery efficiency. The present invention sets a boron diffusion layer under the p-poly, and after the silver paste contacts the p-poly and the boron diffusion, the contact resistance can be significantly reduced. Meanwhile, the contact of the silver paste will not destroy the passivation structure, thus helping to maintain the high performance of the battery.
[0033] As another preferred embodiment, when the P+ layer is a first passivation contact layer formed by in-situ boron doping using PECVD;
[0034] Step S2 includes: preparing SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++) stacked structure, and a mask layer is deposited on the surface. The thickness of the inner layer SiOx1 (first SiOx) is 0.5-2.0 nm, and the p1-poly (p + ) has a thickness of 10-50 nm and a peak concentration of boron atoms of 5×10 18 -5×10 20 atoms / cm 3 , the thickness of SiOx2 is 1-3nm, p2-poly (p ++ ) has a thickness of 50-300 nm and a peak concentration of effective boron atoms of 1×10 19 -5×10 20 atoms / cm 3 , the thickness of the outer mask is 10-100nm BSG.
[0035] SiOx1 / p1-poly(p + ) and SiOx2 / p2-poly (p ++ ) uses BF3 as the boron source; the inner layer SiOx1 / p1-poly (p + ) mainly provides passivation, the outer layer SiOx2 / p2-poly (p ++ ) Improve the conductivity of the contact area. BF3 realizes the layered function of inner layer passivation + outer layer conductivity enhancement during the formation of double-layer poly. The double-layer p-poly structure prepared by BF3 realizes the partition optimization of passivation and contact resistance, which is more suitable for the design requirements of double-sided selective contact batteries.
[0036] The present invention adopts PECVD method to prepare p-poly SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ ) stacked structure, the non-contact area is SiOx2 / p2-poly (p ++ ) is removed, thereby forming a selective contact of poly, and the contact area is SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ ) stacked structure, the non-contact area is SiOx1 / p1-poly (p + ) structure. This allows for good contact and poly thinning. The SiOx / p-poly structure not only helps reduce contact resistance, but also provides a better surface passivation effect, reduces carrier recombination, and improves the open circuit voltage and photoelectric conversion efficiency of the battery.
[0037] S3: Clean and remove the back and surrounding plating to expose the back substrate;
[0038] Preferably, in step S3, chain single-sided HF cleaning is used to remove the BSG layer on the back and surrounding areas, with an HF concentration volume ratio of 30%-50%, and then a mixed acid solution of HF and HNO3 is used for acid polishing to remove the p+ layer and p++ layer on the back and surrounding areas.
[0039] S4: one or two passivation contact layers are sequentially prepared on the back side after S3 treatment, and a mask layer is deposited on the surface at the same time;
[0040] Preferably, in step S4, SiOx / n-poly (n- + ) structure or SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ) laminated structure.
[0041] Conventional single layer SiOx / n-poly (n + ) structured SiOx has a thickness of 1-2nm, n-poly (n + ) thickness is 40-100 nm, and the peak concentration of effective phosphorus atoms is 1-8×10 20 atoms / cm 3 , the inflection point concentration is 5-9×10 18 atoms / cm 3 . SiOx1 / n1-poly(n + ) / SiOx2 / n2-poly(n ++ ) In the stacked structure, the thickness of SiOx1 is 1-2nm, n1-poly (n + ) has a thickness of 10-50 nm and a peak concentration of effective phosphorus atoms of 1-8×10 20 atoms / cm 3 , the inflection point concentration is 5-9×10 18 atoms / cm 3 The thickness of SiOx2 is 1-3nm, n2-poly (n ++ ) has a thickness of 30-80 nm and a peak concentration of effective phosphorus atoms of 1-8×10 20 atoms / cm 3 .
[0042] Among them, when and only when the back side is prepared by in-situ doping using PECVD, annealing is not required after the front side is prepared, and co-annealing treatment is performed with the back side after the back side doping is completed.
[0043] Among them, there are two options for the backside post-operation. One is that the contact area is SiOx1 / n1-poly (n+ ) / SiOx2 / n2-poly(n ++ ) structure, the non-contact area is SiOx1 / n1-poly (n + ), this poly thinning realizes the selective contact of n region. Second, the contact area is SiOx / n-poly (n + ) structure, the non-contact area is passivated with aluminum oxide, which removes the SiOx / n-poly (n + ) implemented poly-finger.
[0044] S5: Use green skin / green nano / purple skin / purple nano lasers to open the film on the front and back non-contact areas, acid wash to remove the plating on the front and surrounding areas, and alkaline wash to remove the second passivation contact layer in the front non-contact area and a passivation contact layer in the back non-contact area; on the front, the passivation layer (SiOx2 / p2-Poly) in the non-contact area is removed by laser to form selective contact. Laser removal enables the contact area to form good contact with the silver paste or electrode in the subsequent process, while the non-contact area remains passivated to reduce carrier recombination. The selective contact on the back also relies on laser opening technology and acid and alkali washing treatment to ensure that the contact area and the non-contact area are separated, avoiding unnecessary current leakage and power loss.
[0045] Preferably, in step S5, the front and back sides are modified with BSG and PSG using green skin / green nano / purple skin / purple nano lasers to loosen or remove the BSG and PSG in the non-contact area, and retain 80-200 μm in the contact area; then pickling is performed to remove the BSG and PSG on the front and surrounding areas; then alkaline washing is performed to remove the n-poly expansion and SiOx2 / p2-poly (p ++ ), and a passivation contact layer in the non-contact area on the back side. If the back side is a single-layer passivation contact layer, it can be polished to the substrate.
[0046] S6: The passivation layer is deposited on both sides in sequence, and then the finished product is obtained after screen printing, sintering and photoelectric injection.
[0047] As a preferred method, the ALD method is used to prepare aluminum oxide passivation on both sides, with an aluminum oxide thickness of 3-10nm; front / back silicon nitride passivation, front silicon nitride anti-reflection, back silicon nitride refraction, followed by screen printing and sintering, LECO laser enhanced passivation contact performance, and finally test sorting. The front and back passivation films (aluminum oxide and silicon nitride) can greatly reduce the surface recombination rate. This passivation effect effectively improves the open circuit voltage (Voc) and short circuit current (Jsc) of the battery, thereby increasing the photoelectric conversion efficiency. Especially in the case of double-sided absorption, both the positive and negative sides are optimized.
[0048] In the present invention, poly-finger is made on both the front and back sides, and the poly layer in the non-contact area is removed to reduce parasitic absorption, while polysilicon (poly-Si) is retained in the contact area to achieve good electrical contact and low recombination rate. While the front poly-finger reduces parasitic absorption and maintains good photoelectric properties, the back side also needs to achieve efficient passivation contact through poly-finger to ensure the matching of double-sided light absorption efficiency.
[0049] When different processes (PECVD or LPCVD) are used on the back side, higher requirements are placed on the compatibility of the front side structure, especially the impact of the high-temperature phosphorus diffusion (>850°C) process on the selective doping of the front poly-finger structure when LPCVD is used on the back side. At this time, the boron atoms in the residual BSG on the front side may diffuse into the non-contact area on the front side, destroying the front poly-finger structure, resulting in a decrease in the passivation effect and an increase in the carrier recombination rate.
[0050] To solve this problem, the passivation layer prepared by BF3 on the front side of the present application has high thermal stability and can maintain structural integrity and passivation effect under high temperature conditions.
[0051] BF3 has high thermal stability as a boron doping source, and the poly Si layer doped with boron can maintain good structural stability under high temperature conditions. It ensures that high efficiency is maintained for a long time in a thinner poly Si layer, while avoiding performance degradation caused by unstable boron doping sources. During the high-temperature phosphorus diffusion process, the passivation layer prepared by BF3 will not release excess boron atoms or cause chemical instability due to thermal decomposition. The effective boron atoms in the passivation layer exist stably in the Si lattice as acceptor impurities and will not be lost or diffused to non-contact areas due to high-temperature treatment.
[0052] In addition, the mask layer on the front side may release a small amount of boron atoms even under high temperature conditions. The p-poly layer prepared by BF3 also has a strong self-passivation ability, which can inhibit the increase of surface recombination caused by it. Even if the LPCVD process is used for high-temperature phosphorus diffusion on the back side, the SiOx / p-poly passivation structure prepared by BF3 on the front side can still maintain a high-efficiency passivation effect, ensuring that the contact resistance and surface recombination rate are not increased due to the presence of the mask layer. And the uniformly doped p-poly layer can still maintain low parasitic absorption after high-temperature treatment, thereby improving the photoelectric conversion efficiency.
[0053] The second object of the present invention is to provide a selectively contacted double-sided TOPCon battery structure having the same technical effect.
[0054] In order to achieve the above object, the technical solution adopted by the present invention is:
[0055] A selectively contacted bifacial TOPCon cell structure includes an N-type silicon substrate;
[0056] The front side of the N-type silicon substrate includes a front contact area and a front non-contact area. The front contact area is provided with a P+ layer, SiOx2 / p2-poly (p ++ ), a front passivation film, a front electrode, and a front non-contact area are provided with a P+ layer and a front passivation film from the inside to the outside;
[0057] The back side of the N-type silicon substrate includes a back contact area and a back non-contact area. The back contact area is provided with SiOx / n-poly (n + ) or SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ )、Back passivation film, back electrode,
[0058] Among them, when the back contact area is provided with SiOx / n-poly (n + ), the back non-contact area is provided with a back passivation film from the inside to the outside; when the back contact area is provided with SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ), the back non-contact area is sequentially provided with SiOx1 / n1-poly (n + ), back side passivation film.
[0059] As a preferred embodiment, the front passivation film and the back passivation film are aluminum oxide and silicon nitride, and the P+ layer is a single boron diffusion or SiOx1 / p1-poly (p + )、SiOx1 / p1-poly(p + ) and SiOx2 / p2-poly (p ++ ) The boron source used is BF3.
[0060] Beneficial effects of the present invention:
[0061] The present invention uses BF3 as a boron doping source to efficiently achieve in-situ boron doping and increase the concentration of boron atoms. The increase in boron atom concentration effectively reduces the contact resistance, thereby optimizing the ohmic contact performance of the battery, especially in the SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ ) combination, this high-efficiency contact significantly improves the battery's current collection capability, thereby improving the battery's efficiency.
[0062] The present invention first prepares a boron diffusion layer on a silicon wafer substrate, and then directly deposits p-poly on the boron diffusion layer, which can ensure good ohmic contact. The boron diffusion layer provides a high-concentration boron-doped region, which helps to improve the contact resistance of the polysilicon layer, so that the contact resistance is significantly reduced. At the same time, the contact of the silver paste will not destroy the original passivation structure, ensuring the stable contact between the silver paste and the passivation contact layer, thereby further reducing the contact resistance and avoiding the problem of reduced battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0064] Figure 1 is a flow chart of the preparation of the battery structure in Example 1 of the present invention;
[0065] Figure 2 is a schematic diagram of the battery structure in Example 1 of the present invention;
[0066] Figure 3 is a schematic diagram of the battery structure in Example 2 of the present invention;
[0067] Figure 4 is a flow chart of the preparation of the battery structure in Example 3 of the present invention;
[0068] Figure 5 is a schematic diagram of the battery structure in Example 3 of the present invention;
[0069] Figure 6 is a schematic diagram of the battery structure in Example 4 of the present invention;
[0070] Reference numerals: 10, N-type silicon substrate; 11, front contact region; 12, front non-contact region; 13, boron diffusion layer; 14, SiOx1 / p1-poly (p + ); 15. SiOx2 / p2-poly (p ++ ); 16, front aluminum oxide passivation film; 17, front silicon nitride passivation film; 18, front electrode; 19, back contact area; 20, back non-contact area; 21, SiOx / n-poly (n + ); 22. SiOx1 / n1-poly (n + ); 23. SiOx2 / n2-poly (n ++ ); 24. Back aluminum oxide passivation film; 25. Back silicon nitride passivation film; 26. Back electrode. DETAILED DESCRIPTION
[0071] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a selectively contacted double-sided TOPCon battery structure and a preparation method thereof proposed in accordance with the present invention, its specific implementation method, characteristics and effects are described in detail as follows.
[0072] In the examples of the present invention, the sources of commercially available materials are as follows:
[0073]
[0074] Embodiment 1:
[0075] A selectively contacted double-sided TOPCon cell structure includes an N-type silicon substrate 10;
[0076] The front side of the N-type silicon substrate 10 includes a front contact area 11 and a front non-contact area 12. The front contact area 11 is provided with a boron diffusion layer 13, a SiOx2 / p2-poly (p ++ ) 15, a front aluminum oxide passivation film 16, a front silicon nitride passivation film 17, and a front electrode 18. The front non-contact area 12 is provided with a boron diffusion layer 13, a front aluminum oxide passivation film 16, and a front silicon nitride passivation film 17 in sequence from the inside to the outside;
[0077] The back side of the N-type silicon substrate 10 includes a back side contact area 19 and a back side non-contact area 20. The back side contact area 19 is provided with SiOx / n-poly (n + ) 21, a back aluminum oxide passivation film 24, a back silicon nitride passivation film 25, and a back electrode 26. The back non-contact area 20 is sequentially provided with a back aluminum oxide passivation film 24 and a back silicon nitride passivation film 25 from the inside to the outside.
[0078] A method for preparing a selectively contacted double-sided TOPCon battery structure comprises the following steps:
[0079] S1: Select N-type silicon wafers with a resistivity of 0.5-2Ω.cm and a minority carrier lifetime of >10ms as the battery substrate, perform double-sided texturing to remove damage and form a pyramid structure for surface light trapping, use a texturing liquid (KOH: additive = 6:1), maintain the temperature at 80℃, and perform rapid texturing for about 5 minutes. The thinning amount is controlled at 0.2g.
[0080] S2: Boron diffusion is first performed on the textured surface on the front side of the substrate, and then a second passivation contact layer is formed by in-situ boron doping using PECVD, and a mask layer is deposited on the surface at the same time; BF3 is used as a boron source for the second passivation contact layer;
[0081] (1) Boron doping was performed using a high-temperature furnace tube, and the doping advancement and oxidation were performed at a temperature of 1050°C. The BSG thickness was controlled at 120nm, the doping square resistance was controlled at 350ohm / sq, and the peak concentration of boron atoms was 3×10 18 atoms / cm 3 .
[0082] (2) Use green laser to modify BSG, loosen or remove the BSG in the contact area. The laser area is the grid line printing area, and 100um is removed, while the non-laser area is retained.
[0083] (3) Use trough HF (4%) dip cleaning to remove BSG in the laser area.
[0084] (4) Preparation of SiOx / p-poly(p ++ ) structure, and a mask layer is deposited on the surface, where the thickness of SiOx is 1.5nm, p-poly (p ++ ) has a thickness of 90 nm and a peak concentration of effective boron atoms of 3×10 20 atoms / cm 3 , the thickness of the outer mask is 40nm BSG.
[0085] S3: Clean and remove the back and surrounding plating to expose the back substrate; first use a chain cleaning machine with a HF concentration volume ratio (40%) to remove the BSG layer on the front and side, and then use a mixed acid solution of HF and HNO3 to acid polish to remove the B expansion on the back and surrounding (p + ) layer and SiOx / p-poly (p ++ )layer.
[0086] S4: A single layer of SiOx / n-poly-Si was prepared on the back side after S3 treatment by LPCVD+phosphorus diffusion or PECVD+annealing, and a mask layer was deposited on the surface; the thickness of the single layer of SiOx was 1.5nm, the thickness of n-poly-Si was 80nm, and the peak concentration of effective phosphorus atoms was 4×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 .
[0087] S5: Use green laser to modify BSG and PSG in the non-contact area on the front and back, loosen or remove the BSG and PSG in the non-contact area. The non-laser area is the grid line printing area, and the non-laser area retains 100μm. Use a chain cleaning machine with a HF concentration volume ratio of 15% to remove the BSG and PSG layers on the front and side, and alkaline washing to remove the n-poly expansion and p-poly-Si (p ++ ) / SiOx, SiOx / poly-Si(n) in the back laser area, and the back side is polished to the substrate.
[0088] S6: Aluminum oxide passivation is prepared on both sides by ALD method, and the thickness of aluminum oxide is 5nm. Then silicon nitride passivation is prepared on both sides, with silicon nitride anti-reflection on the front side and silicon nitride refraction on the back side; the total film thickness is 83nm, and the refractive index is 1.99; the front / back electrode is printed, sintered, and the LECO laser is used to enhance the passivation contact performance, and finally tested and sorted.
[0089] Embodiment 2:
[0090] A selectively contacted double-sided TOPCon cell structure includes an N-type silicon substrate 10;
[0091] The front side of the N-type silicon substrate 10 includes a front contact area 11 and a front non-contact area 12. The front contact area 11 is provided with a boron diffusion layer 13, a SiOx2 / p2-poly (p ++ ) 15, a front aluminum oxide passivation film 16, a front silicon nitride passivation film 17, and a front electrode 18. The front non-contact area 12 is provided with a boron diffusion layer 13, a front aluminum oxide passivation film 16, and a front silicon nitride passivation film 17 in sequence from the inside to the outside;
[0092] The back side of the N-type silicon substrate 10 includes a back side contact area 19 and a back side non-contact area 20. The back side contact area 19 is provided with SiOx1 / n1-poly (n + ) 22. SiOx2 / n2-poly (n ++ ) 23, back aluminum oxide passivation film 24, back silicon nitride passivation film 25, back electrode 26, the back non-contact area 20 is sequentially provided with SiOx1 / n1-poly (n + ) 22, back aluminum oxide passivation film 24, back silicon nitride passivation film 25.
[0093] A method for preparing a selectively contacted double-sided TOPCon battery structure comprises the following steps:
[0094] S1: Select N-type silicon wafers with a resistivity of 0.5-2Ω.cm and a minority carrier lifetime of >10ms as the battery substrate, perform double-sided texturing to remove damage and form a pyramid structure for surface light trapping, use a texturing liquid (KOH: additive = 6:1), maintain the temperature at 80℃, and perform rapid texturing for about 5 minutes. The thinning amount is controlled at 0.2g.
[0095] S2: Boron diffusion is first performed on the textured surface on the front side of the substrate, and then a second passivation contact layer is formed by in-situ boron doping using PECVD, and a mask layer is deposited on the surface at the same time; BF3 is used as a boron source for the second passivation contact layer;
[0096] (1) Boron doping was performed using a high-temperature furnace tube, and the doping advancement and oxidation were performed at a temperature of 1050°C. The BSG thickness was controlled at 120nm, the doping square resistance was controlled at 350ohm / sq, and the peak concentration of boron atoms was 3×10 18 atoms / cm 3 .
[0097] (2) Use green laser to modify BSG, loosen or remove the BSG in the contact area. The laser area is the grid line printing area, and 100um is removed, while the non-laser area is retained.
[0098] (3) Use trough HF (4%) dip cleaning to remove BSG in the laser area.
[0099] (4) Preparation of SiOx / p-poly(p ++ ) structure, and a mask layer is deposited on the surface, where the thickness of SiOx is 1.5nm, p-poly (p ++ ) has a thickness of 90 nm and a peak concentration of effective boron atoms of 3×10 20 atoms / cm 3 , the thickness of the outer mask is 40nm BSG.
[0100] S3: Clean and remove the back and surrounding plating to expose the back substrate; first use a chain cleaning machine with a HF concentration volume ratio (40%) to remove the BSG layer on the front and side, and then use a mixed acid solution of HF and HNO3 to acid polish to remove the B expansion on the back and surrounding (p + ) layer and SiOx / p-poly (p ++ )layer.
[0101] S4: Prepare the back structure by LPCVD+phosphorus diffusion or PECVD+annealing. The back structure is SiOx1 / n1-poly(n + ) / SiOx2 / n2-poly(n ++) stacked structure. SiOx1 / n1-poly(n + ) / SiOx2 / n2-poly(n ++ ) stacked structure, the thickness of SiOx1 is 1.5nm, n1-poly(n + ) is 30 nm thick and the peak concentration of effective phosphorus atoms is 3×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 The thickness of SiOx2 is 1.5nm, n2-poly(n ++ ) is 50 nm thick and the peak concentration of effective phosphorus atoms is 4×10 20 atoms / cm 3 .
[0102] S5: Use green laser to modify BSG and PSG in the non-contact area on the front and back, loosen or remove the BSG and PSG in the non-contact area. The non-laser area is the grid line printing area, and the non-laser area retains 100μm. Use a chain cleaning machine with a HF concentration volume ratio of 15% to remove the BSG and PSG layers on the front and side, and alkaline washing to remove the n-poly expansion and p-poly (p ++ ) / SiOx, n2-poly (n ++ ) / SiOx2.
[0103] S6: Aluminum oxide passivation is prepared on both sides by ALD method, and the thickness of aluminum oxide is 5nm. Then silicon nitride passivation is prepared on both sides, with silicon nitride anti-reflection on the front side and silicon nitride refraction on the back side; the total film thickness is 83nm, and the refractive index is 1.99; the front / back electrode is printed, sintered, and the LECO laser is used to enhance the passivation contact performance, and finally tested and sorted.
[0104] Embodiment 3:
[0105] A selectively contacted double-sided TOPCon cell structure includes an N-type silicon substrate 10;
[0106] The front side of the N-type silicon substrate 10 includes a front contact area 11 and a front non-contact area 12. The front contact area 11 is provided with SiOx1 / p1-poly (p + )14.SiOx2 / p2-poly (p ++ ) 15, front aluminum oxide passivation film 16, front silicon nitride passivation film 17, front electrode 18, the front non-contact area 12 is sequentially provided with SiOx1 / p1-poly (p + ) 14, front aluminum oxide passivation film 16, front silicon nitride passivation film 17;
[0107] The back side of the N-type silicon substrate 10 includes a back side contact area 19 and a back side non-contact area 20. The back side contact area 19 is provided with SiOx / n-poly (n + ) 21, a back aluminum oxide passivation film 24, a back silicon nitride passivation film 25, and a back electrode 26. The back non-contact area 20 is sequentially provided with a back aluminum oxide passivation film 24 and a back silicon nitride passivation film 25 from the inside to the outside.
[0108] A method for preparing a selectively contacted double-sided TOPCon battery structure comprises the following steps:
[0109] S1: Select N-type silicon wafers with a resistivity of 0.5-2Ω.cm and a minority carrier lifetime of >10ms as the battery substrate, perform double-sided texturing to remove damage and form a pyramid structure for surface light trapping, use a texturing liquid (KOH: additive = 6:1), maintain the temperature at 80℃, and perform rapid texturing for about 5 minutes. The thinning amount is controlled at 0.2g.
[0110] S2: SiOx1 / p1-poly(p + ) / SiOx2 / p2-poly(p ++ ) stacked structure, and a mask is deposited on the surface at the same time, where the inner layer SiOx1 (first SiOx) has a thickness of 1.5nm, p1-poly (p + ) is 40 nm thick and the peak concentration of boron atoms is 1×10 20 atoms / cm 3 The thickness of the second SiOx2 is 1.5nm, p2-poly (p ++ ) has a thickness of 90 nm and a peak concentration of effective boron atoms of 3×10 20 atoms / cm 3 , the thickness of the outer mask is 40nm BSG.
[0111] S3: Clean and remove the back and surrounding plating to expose the back substrate; first use a chain cleaning machine with a HF concentration volume ratio (40%) to remove the BSG layer on the back and sides, and then use a mixed acid solution of HF and HNO3 to acid polish to remove the SiOx1 / p1-poly (p + ) layer and SiOx2 / p2-poly (p ++ )layer.
[0112] S4: The back side structure is prepared by PECVD+annealing. The back side structure is a conventional single-layer SiOx / n-poly. The thickness of the conventional single-layer SiOx is 1.5nm, the thickness of the n-poly is 80nm, and the peak concentration of effective phosphorus atoms is 4×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 .
[0113] S5: Use green laser to modify BSG and PSG in the non-contact area on the front and back, loosen or remove the BSG and PSG in the non-contact area. The non-laser area is the grid line printing area, and the non-laser area retains 100μm. Use a chain cleaning machine with a HF concentration volume ratio of 15% to remove the BSG and PSG layers on the front and side, and alkaline washing to remove the n-poly expansion and p-poly (p ++ ) / SiOx, SiOx / n-poly in the back laser area, and polished to the substrate on the back side.
[0114] S6: Aluminum oxide passivation is prepared on both sides by ALD method, and the thickness of aluminum oxide is 6nm. Then silicon nitride passivation is prepared on both sides, with silicon nitride anti-reflection on the front side and silicon nitride refraction on the back side; the total film thickness is 83nm, and the refractive index is 1.99; the front / back electrode is printed, sintered, and the LECO laser is used to enhance the passivation contact performance, and finally tested and sorted.
[0115] Embodiment 4:
[0116] A selectively contacted double-sided TOPCon cell structure includes an N-type silicon substrate 10;
[0117] The front side of the N-type silicon substrate 10 includes a front contact area 11 and a front non-contact area 12. The front contact area 11 is provided with SiOx1 / p1-poly (p + )14.SiOx2 / p2-poly (p ++ ) 15, front aluminum oxide passivation film 16, front silicon nitride passivation film 17, front electrode 18, the front non-contact area 12 is sequentially provided with SiOx1 / p1-poly (p + ) 14, front aluminum oxide passivation film 16, front silicon nitride passivation film 17;
[0118] The back side of the N-type silicon substrate 10 includes a back side contact area 19 and a back side non-contact area 20. The back side contact area 19 is provided with SiOx1 / n1-poly (n + ) 22. SiOx2 / n2-poly (n ++) 23, back aluminum oxide passivation film 24, back silicon nitride passivation film 25, back electrode 26, the back non-contact area 20 is sequentially provided with SiOx1 / n1-poly (n + ) 22, back aluminum oxide passivation film 24, back silicon nitride passivation film 25.
[0119] A method for preparing a selectively contacted double-sided TOPCon battery structure comprises the following steps:
[0120] S1: Select N-type silicon wafers with a resistivity of 0.5-2Ω.cm and a minority carrier lifetime of >10ms as the battery substrate, perform double-sided texturing to remove damage and form a pyramid structure for surface light trapping, use a texturing liquid (KOH: additive = 6:1), maintain the temperature at 80℃, and perform rapid texturing for about 5 minutes. The thinning amount is controlled at 0.2g.
[0121] S2: SiOx1 / p1-poly(p + ) / SiOx2 / p2-poly(p ++ ) stacked structure, and a mask is deposited on the surface at the same time, where the inner layer SiOx1 (first SiOx) is 1.5nm thick, the p1-poly (p+) is 40nm thick, and the peak concentration of boron atoms is 1×10 20 atoms / cm 3 The thickness of the second SiOx2 is 1.5nm, p2-poly (p ++ ) has a thickness of 90 nm and a peak concentration of effective boron atoms of 3×10 20 atoms / cm 3 , the thickness of the outer mask is 40nm BSG.
[0122] S3: Clean and remove the back and surrounding plating to expose the back substrate; first use a chain cleaning machine with a HF concentration volume ratio (40%) to remove the BSG layer on the back and sides, and then use a mixed acid solution of HF and HNO3 to acid polish to remove the SiOx1 / p1-poly (p + ) layer and SiOx2 / p2-poly(p ++ )layer.
[0123] S4: The back side structure is prepared by PECVD+annealing. The back side structure is SiOx1 / n1-poly(n + ) / SiOx2 / n2-poly(n ++ ) stacked structure. In SiOx1 / n1-poly(n +) / SiOx2 / n2-poly(n ++ ) stacked structure, the thickness of SiOx1 is 1.5nm, n1-poly(n + ) is 30 nm thick and the peak concentration of effective phosphorus atoms is 3×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 The thickness of SiOx2 is 1.5nm, n2-poly(n ++ ) is 50 nm thick and the peak concentration of effective phosphorus atoms is 4×10 20 atoms / cm 3 .
[0124] S5: Use green laser to modify BSG and PSG in the non-contact area on the front and back, loosen or remove the BSG and PSG in the non-contact area. The non-laser area is the grid line printing area, and the non-laser area retains 100μm. Use a chain cleaning machine with a HF concentration volume ratio of 15% to remove the BSG and PSG layers on the front and side, and alkaline washing to remove the n-poly expansion and p-poly (p ++ ) / SiOx2, n2-poly (n ++ ) / SiOx2.
[0125] S6: Aluminum oxide passivation is prepared on both sides by ALD method, and the thickness of aluminum oxide is 6nm. Then silicon nitride passivation is prepared on both sides, with silicon nitride anti-reflection on the front side and silicon nitride refraction on the back side; the total film thickness is 83nm, and the refractive index is 1.99; the front / back electrode is printed, sintered, and the LECO laser is used to enhance the passivation contact performance, and finally tested and sorted.
[0126] Comparative Example 1:
[0127] The difference between this comparative example and Example 1 is that PECVD in-situ doping is directly performed on the front side after texturing:
[0128] 2) Front PECVD in-situ doping - preparation of SiOx / p-poly (p ++ ) structure, and a mask layer is deposited on the surface, where the thickness of SiOx is 1.5nm, p-poly (p ++ ) has a thickness of 90nm and an outer mask of 40nm BSG.
[0129] Battery performance test results:
[0130] The blue diaphragm structure of the embodiment was characterized, that is, the test was performed before the electrode was prepared, and the performance test results are shown in Table 1: This data is the blue diaphragm data of the battery structure, and the data can reflect that the solution is feasible.
[0131] Table 1
[0132]
[0133] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a selectively contacted double-sided TOPCon battery structure, characterized in that: The steps are as follows: S1: Select N-type silicon wafer as the battery substrate and perform double-sided texturing; S2: sequentially forming a P+ layer and a P++ layer on the textured surface of the front side of the substrate, and depositing a mask layer on the surface; wherein the P+ layer is a boron diffusion layer or a first passivation contact layer formed by in-situ boron doping using a PECVD method, and the P++ layer is a second passivation contact layer formed by in-situ boron doping using a PECVD method; the first passivation contact layer and the second passivation contact layer use BF3 as a boron source; S3: Clean and remove the back and surrounding plating to expose the back substrate; S4: preparing an N+ layer on the back side after the S3 treatment, and depositing a mask layer on the surface; the N+ layer is a single-layer passivation contact layer or a double-layer passivation contact layer; S5: Use laser to open the film on the front and back non-contact areas, pickle to remove the plating on the front and surrounding areas, and alkaline to remove the second passivation contact layer on the front non-contact area and a passivation contact layer on the back non-contact area; S6: Depositing passivation layers on both sides in sequence, followed by screen printing, sintering and photoelectric injection to obtain a finished product; The first passivation contact layer is SiOx1 / p1-poly (p + ), the second passivation contact layer is SiOx2 / p2-poly (p ++ ); When the N+ layer is a single-layer passivation contact layer, the single-layer passivation contact layer is SiOx / n-poly (n + ); When the N+ layer is a double-layer passivation contact layer, the double-layer passivation contact layer is SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ).
2. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 1, characterized in that: When the P+ layer is a boron diffusion layer, step S2 includes: Boron diffusion is performed on the textured surface on the front side of the substrate to form a PN junction; Use laser to open the film on the front contact area; clean and remove the BSG in the contact area; Then, SiOx2 / p2-poly (p ++ ), and a mask layer is deposited on the surface at the same time.
3. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 2, characterized in that: The boron doping and oxidation are carried out at a temperature of 850-1100℃ on the textured surface of the substrate. The BSG thickness is controlled at 90-150nm, the doping square resistance is controlled at 200-400ohm / sq, and the peak concentration of boron atoms is 1×10 18 -1×10 19 atoms / cm 3 ; Then use laser to modify BSG in the front contact area to loosen or remove the BSG in the contact area. The width of the contact area is 80-200um, and pickling is used to remove the BSG in the contact area.
4. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 1, characterized in that: When the P+ layer is a first passivation contact layer formed by in-situ doping using PECVD, step S2 includes: preparing SiOx1 / p1-poly (p + ) / SiOx2 / p2-poly(p ++ )’s stacked structure, and a mask layer is deposited on the surface at the same time.
5. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 2 or 4, characterized in that: In step S3, chain single-sided HF cleaning is used to remove the BSG layer on the back and surrounding areas, and then a mixed acid solution of HF and HNO3 is used for acid polishing to remove the p+ layer and p++ layer on the back and surrounding areas.
6. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 1, characterized in that: In step S4, SiOx / n-poly (n-poly) is prepared on the back side after the treatment in step S3 by LPCVD+phosphorus diffusion or PECVD+phosphorus doping annealing. + ) structure or SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ) laminated structure.
7. The method for preparing a selectively contacted double-sided TOPCon battery structure according to claim 1, characterized in that: In step S5, lasers are used to modify BSG and PSG on the front and back sides, loosening or removing the BSG and PSG in the non-contact area, and retaining 80-200 μm in the contact area; then pickling is performed to remove the BSG and PSG on the front and surrounding areas; then alkaline washing is performed to remove the n-poly expansion and SiOx2 / p2-poly (p ++ ), and a passivation contact layer on the back non-contact area. If the back side is a single-layer passivation contact layer, it is polished to the substrate.
8. A selectively contacted double-sided TOPCon cell structure prepared by the method according to claim 1, characterized in that: including an N-type silicon substrate; The front side of the N-type silicon substrate includes a front contact area and a front non-contact area, wherein the front contact area is provided with a P+ layer, SiOx2 / p2-poly (p ++ ), a front passivation film, and a front electrode, wherein the front non-contact area is provided with a P+ layer and a front passivation film in sequence from the inside to the outside; The back side of the N-type silicon substrate includes a back contact area and a back non-contact area, wherein the back contact area is provided with SiOx / n-poly (n + ) or SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ )、Back passivation film, back electrode, Wherein, the P+ layer is a single boron diffusion or SiOx1 / p1-poly (p + ), when the back contact area is provided with SiOx / n-poly (n + ), the back non-contact area is provided with a back passivation film from the inside to the outside; when the back contact area is provided with SiOx1 / n1-poly (n + ) / SiOx2 / n2-poly(n ++ ), the back non-contact area is sequentially provided with SiOx1 / n1-poly (n + ), back side passivation film.
9. A selectively contacted double-sided TOPCon battery structure according to claim 8, characterized in that: The front passivation film and the back passivation film are aluminum oxide and silicon nitride.
Citation Information
Patent Citations
Selective passivation contact battery and preparation method thereof
CN115020507A
Tunnel oxide passivation contact solar cell and preparation method thereof
CN116799073A